2018
DOI: 10.1080/07420528.2018.1500477
|View full text |Cite
|
Sign up to set email alerts
|

The synchrony effect revisited: chronotype, time of day and cognitive performance in a semantic analogy task

Abstract: The synchrony effect (i.e. superior performance at optimal, inferior performance at suboptimal times of day) has been broadly studied within the context of circadian rhythms. Whether one chronotype copes better with the synchrony effect than the other received only insufficient empirical attention. We report on an applied experimental study investigating the impact of chronotype on the synchrony effect in a semantic analogy task. To detect an analogy, 36 participants (12 males) aged between 18 and 40 had to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…An evening circadian preference, also called extreme eveningness or evening chronotype, is hypothesized to be a proxy marker of circadian system dysfunction because of its association with circadian phase delay (23). A desynchronization between the components of the circadian system favored by a circadian phase delay in individuals with an evening chronotype may represent a potential mechanism for the associated adverse health outcomes (24)(25)(26)(27). Indeed, evening chronotype is associated with disorganized eating behavior, unhealthy food preferences, nighteating behavior, and binge-eating behavior (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…An evening circadian preference, also called extreme eveningness or evening chronotype, is hypothesized to be a proxy marker of circadian system dysfunction because of its association with circadian phase delay (23). A desynchronization between the components of the circadian system favored by a circadian phase delay in individuals with an evening chronotype may represent a potential mechanism for the associated adverse health outcomes (24)(25)(26)(27). Indeed, evening chronotype is associated with disorganized eating behavior, unhealthy food preferences, nighteating behavior, and binge-eating behavior (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…At optimal times of day, M-types had more cognitive resources available to allocate in the case of more demanding conditions. E-types appear less able to adapt to suboptimal times, because they have to deal with social jetlag and decreased self-control [7]. In fact, a recent systematic review reported that female nurses with an evening-oriented preference suffer more problems of insomnia, sleepiness, fatigue, and anxiety [8].…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, the synchrony effect is often construed as a cyclic variation in the amount of available cognitive resources (e.g., Nowack & Van Der Meer, 2018). We subjectively experience circadian arousal cycles as changes in energy levels throughout the day (Cariou, Galy, & Mélan, 2008;Thayer, 1987).…”
Section: The Circadian Rhythm and Memory Performancementioning
confidence: 99%
“…Inter-individual differences in the functioning of the body clock can be an important factor determining the time of day that is most optimal in terms of cognitive performance. Across a wide range of cognitive domains, such as attentional capacities, working and long-term memory, inhibition of irrelevant responses, and avoidance of stereotype-based responses, morning types perform better in the morning, and, the other way around, evening types are better in the evening (e.g., Goldstein, Hahn, Hasher, Wiprzycka, & Zelazo, 2007;May 1999;Nowack & Van Der Meer, 2018). Likewise, episodic memory is subject to the synchrony effect: Experimental research to date suggests that recall and recognition performance is better at circadian peaks as opposed to circadian troughs (May, Hasher, & Stoltzfus, 1993;Ryan, Hatfield, & Hofstetter, 2002;Petros, Beckwith, & Anderson, 1990;Yoon, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation